Innovation Platforms for Agricultural Development: A Case Study of SIDS Research Station in Egypt - Salem, Shaban Ali; M. Oumer, Ali; Dhehibi, Boubaker; Abda-Allah Abdallah, Iman; Souissi, Asma; Baum, Michael (2024)
The objective of this research was to review Innovation Platforms (IPs) and their roles in agricultural development and characterize SIDS Research Station to evaluate its potential as a national IP in Egypt. Literature review results indicate that IPs have several functions to stimulate research and development around the world. For example, IPs can help test scientific ideas, technologies, and innovations. These are particularly effective when farming challenges require joint efforts of stakeholders. In this regard, IPs can help stakeholders experiment together and share knowledge, resources, benefits, and risks for issues they cannot solve on their own, and benefit from the synergistic effects of working together. The results of the research station characterization indicate that SIDS Research Station has huge potential as a national innovation platform in Egypt. Therefore, the Agricultural Research Center (ARC) of Egypt can take the initiate to set up the national IP by engaging diverse stakeholders of both public and private sector actors.